Childhood adversities and adult-onset asthma: a cohort study - Jyrki Korkeila; Raija Lietzen; Lauri H Sillanmäki; Päivi Rautava; Katariina Korkeila; Mika Kivimäki; Markku Koskenvuo; Jussi Vahtera (BMJ PUBLISHING GROUP, 2022)
Conclusions: Adults who report having encountered adversities in childhood may have an increased risk of developing asthma.